2015
DOI: 10.1186/s12955-015-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton depression rating scale and montgomery–asberg depression rating scale in depressed and bipolar I patients: psychometric properties in a Brazilian sample

Abstract: BackgroundThe Hamilton Depression Rating Scale (HAM-D) and the Montgomery–Asberg Depression Scale (MADRS) are used worldwide and considered standard scales for evaluating depressive symptoms. This paper aims to investigate the psychometric proprieties (reliability and validity) of these scales in a Brazilian sample, and to compare responses in bipolar and unipolar patients.MethodsThe sample comprised 91 patients with either bipolar I or major depressive disorder from a psychiatric institute at São Paulo, Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…The cut-off points for different levels of depression were as follows: 0 to 6 = not depressed; 7 to 17 = mildly depressed; 18 to 24 = moderately depressed; and 25 to 64 = severely depressed (20). Carnerio, Fernandes, and Moreno, reported adequate reliability (a = 0.83) and validity for this scale (21). In Iran, Mokhber, Azar Pajooh, and Asgharipour (22) reported the reliability of this scale via correlation with BDI as 0.90 and high validity.…”
Section: Study Toolsmentioning
confidence: 99%
“…The cut-off points for different levels of depression were as follows: 0 to 6 = not depressed; 7 to 17 = mildly depressed; 18 to 24 = moderately depressed; and 25 to 64 = severely depressed (20). Carnerio, Fernandes, and Moreno, reported adequate reliability (a = 0.83) and validity for this scale (21). In Iran, Mokhber, Azar Pajooh, and Asgharipour (22) reported the reliability of this scale via correlation with BDI as 0.90 and high validity.…”
Section: Study Toolsmentioning
confidence: 99%
“…Carneiro et al [107] showed that only 4 items of the unstructured HAM-D 17 (i.e., insomnia late, general somatic symptoms, hypochondriasis, and insight) sensitively discriminated depressed patients from bipolar I patients.…”
Section: Different Groups Of Patientsmentioning
confidence: 99%
“…Another tool included the Beck Depression Inventory that uses a patient self-reporting tool of depressive symptoms [14]. These tools demonstrated high sensitivity and specificity and therefore are the best validated scales used for assessing the degree of severity of depressive symptoms [14, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%